(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Politicians are notorious for their employment of words in a disguised fashion through the usage of euphemisms. Consequently, their messagebecomes a recurrent theme of conspicuous deception. Electedgovernment representatives deliberately engage in grandiloquent expression consciousof its subversivecapacity. The deviancy of euphemisms is guided by socialnorms that politicians are permitted to exercise inorder tosafeguard their images. When politiciansenvelop seemingly good intentionswith consciousdeception,people are harmed in the process. Those in power transgress justice and commit crimes with their overwhelming command of euphemisms. In fact, euphemisms are utilized asmasks, hiding truths underthe protective tones of a speaker with a genuine, worthwhile goal. Selective vocabulary is employedto arouse,rationalize and justify. To achieve this end, politicians misrepresent the facts of various political situations by using terms that completely transform or falsify them. Euphemisms are used simplistically in daily conversations. However, where they are used and misused more frequently is in the political arena, in such cases as “soft targets” or “peace keepers” or “collateral damage.” These expressions are heard frequently,while past ones are forgotten and new ones primed in their place as transgressions continue. In this paper, Iwill make useof Jurgen Habermas’public sphere theory,a critical theory that demonstrates how theaudience’s outlook affectspolitical action. Thisarticle will demonstrate the deliberate use ofeuphemisms in political language both as a cultural elementand as one that is constantly changing to suit the ever-changing politicalarena.